2017
DOI: 10.1097/fbp.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with fish oil prevents high fat diet-induced enhancement of sensitivity to the behavioral effects of quinpirole

Abstract: Consuming a high fat diet can lead to many negative health consequences, such as obesity, insulin resistance, and enhanced sensitivity to drugs acting on dopamine systems. It has recently been demonstrated that dietary supplementation with fish oil, which is rich in omega-3 fatty acids, can prevent this high fat diet-induced enhanced sensitivity to dopaminergic drugs from developing. However, it is not known if fish oil supplementation can reverse this effect once it has already developed. In order to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Rats eating high fat chow weighed significantly more than rats in all other dietary groups, although all subjects gained weight throughout the study (see Figure 1A). Even though rats eating standard chow supplemented with fish oil gained less weight throughout the experiment than rats eating high fat chow, or high fat chow with fish oil, they consumed the most amount of kcal per day on average of any group (similar to what has been reported previously, Hernandez-Casner et al, 2017). Greater kcal intake does not correlate with greater body weight; therefore, it is possible that fish oil supplementation is impacting metabolism.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Rats eating high fat chow weighed significantly more than rats in all other dietary groups, although all subjects gained weight throughout the study (see Figure 1A). Even though rats eating standard chow supplemented with fish oil gained less weight throughout the experiment than rats eating high fat chow, or high fat chow with fish oil, they consumed the most amount of kcal per day on average of any group (similar to what has been reported previously, Hernandez-Casner et al, 2017). Greater kcal intake does not correlate with greater body weight; therefore, it is possible that fish oil supplementation is impacting metabolism.…”
Section: Discussionsupporting
confidence: 78%
“…In previous reports, when fish oil was added directly to the high fat chow, rats never developed enhanced sensitivity to the behavioral effects of dopaminergic drugs (Hernandez-Casner et al, 2017;Serafine et al, 2016). In other words, dietary supplementation with fish oil prevented high fat chow-induced enhanced sensitivity to quinpirole (Hernandez-Casner et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…One potential factor that might underly the discordant results in the literature regarding receptor expression changes is body weight itself. For example, it has been well demonstrated that eating a high fat diet produces changes to drug sensitivity, similar to those demonstrated in this report, even in the absence of changes to body weight (Ramos et al, 2019;Baladi et al, 2011;Hernandez-Casner et al, 2019). In contrast, many of the reports demonstrating changes in dopamine receptor expression also describe increases in body weight among animals eating a high fat diet (Johnson and Kenny, 2010;South and Huang, 2008;Konner et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…Further, changes to dopamine D2 receptor binding has also been demonstrated among obese human patients (Tomasi and Volkow, 2013;Wang et al, 2001;de Weijer et al, 2011). Although the rats in the present experiments were not definable as obese by many recognized definitions, we have previously demonstrated that body fact composition can be altered even in the absence of changes to overall body weight (Hernandez-Casner et al, 2019). Future research will explore the possible factors involved in weight gain versus body fat distribution changes that might be occurring concurrent to changes in dopamine receptor expression and sensitivity.…”
Section: Discussionsupporting
confidence: 41%